Multiwalled carbon nanotube/chitosan composite on quartz crystal microbalance for formaldehyde detection - Mahadi, Aisyah Syafiqah; Razib, Mohd Asyraf Mohd; Ralib, Aliza Aini Md; Ahmad, Farah; Yusof, Marmeezee Mohd. (Bulletin of Electrical Engineering and Informatics, 2025)
This study introduces multi-walled carbon nanotubes (MWCNT)/chitosan (CS) composite as a potential new sensing material for quartz crystal microbalance (QCM) formaldehyde sensors. This sensing material selectively binds target molecules, causing a measurable frequency shift proportional to the added mass. CS, MWCNT, and the MWCNT/Cs composite samples were prepared for comparison via sonification, crosslinking and dispersion methods. The morphology character was studied using Raman spectroscopy, Fourier transform infrared (FTIR) spectroscopy, and field emission scanning electron microscopy (FE-SEM). Next the samples were drop cast on the QCM working electrode. An adsorption test was conducted to study the static and dynamic response for the formaldehyde detection. The frequency shift of the formaldehyde adsorption for the CS, MWCNT-COOH, and MWCNT/CS-based sensors were 114.98 Hz, 108.23 Hz, and 196.63 Hz respectively. The calculated sensitivity of 23.48 Hz/ppm and regression line R2 at 0.95076 were recorded shows that the MWCNT/CS can be a promising sensing layer to detect formaldehyde vapour.